MENGATASI KEMACETAN DI LAMPU MERAH DENGAN PENDEKATAN IMAGE PROCESSING - Ismail Setiawan (Journal of Innovation And Future Technology (IFTECH), 2022)
The phenomenon of congestion in a big city is generally caused by the large number of vehicles while roads do not develop every year. The growth in the number of vehicles on the highway contributes to a large number of causes of congestion. Congestion often occurs at red light intersections. Various solutions have been implemented such as limiting the number of vehicles based on odd-even numbers by date, limiting motorized vehicles such as motorbikes that are not allowed to pass through the main road, increasing the number of public vehicles and arranging the departure schedule for school children and office employees. The solution has been carried out but there are still long queues of vehicles. One of the reasons for this is because the number of vehicle queues is long while the timer that shows the time to walk or the green light is short. Intelligent systems technology-based approach can be used to overcome these problems. Because humans have limitations to do so, the task can be done by computers. The result of this activity is that the right camera position is next to the traffic timer and the best time to read the image is during the day